Bed elevation of Jakobshavn Isbræ, West Greenland, from high‐resolution airborne gravity and other data. Issue 8 (30th April 2017) - An, L.; Rignot, E.; Elieff, S.; Morlighem, M.; Millan, R.; Mouginot, J.; Holland, D. M.; Holland, D.; Paden, J.
Abstract: Jakobshavn Isbræ, West Greenland, which holds a 0.6 m sea level volume equivalent, has been speeding up and retreating since the late 1990s. Interpretation of its retreat has been hindered by difficulties in measuring its ice thickness with airborne radar depth sounders. Here we employ high‐resolution, helicopter‐borne gravity data from 2012 to reconstruct its bed elevation within 50 km of the ocean margin using a three‐dimensional inversion constrained by fjord bathymetry data offshore and a mass conservation algorithm inland. We find the glacier trough to be asymmetric and several 100 m deeper than estimated previously in the lower part. From 1996 to 2016, the grounding line migrated at 0.6 km/yr from 700 m to 1100 m depth. Upstream, the bed drops to 1600 m over 10 km then slowly climbs to 1200 m depth in 40 km. Jakobshavn Isbræ will continue to retreat along a retrograde slope for decades to come. Key Points: We combine airborne gravity with other data to provide a more definite view of the bed topography of a major outlet glacier in Greenland Based on the refined bed topography, we project that Jakobshavn Isbræ will keep retreating into deeper grounds for decades to come High‐resolution gravity data helps fill gaps in major outlet glacier bed mapping where traditional deep radar sounding methods fail